Rethinking Islamic Political Thought in Contemporary Muslim Societies - Muhammad Alfi Syahrin; Khoiriyah; Heri Rifhan Halili; Babussalam (PT. Education Research Center, 2025)
Contemporary Muslim societies face political transformation involving democracy, citizenship, religious authority, state power, and public ethics. Debates on Islamic politics often remain polarized between formalistic legalism and secular exclusion, making contextual reconstruction necessary. This study aims to formulate a renewed framework of Islamic political thought that connects classical Islamic principles with contemporary civic realities. This research used a qualitative conceptual design with a library research approach. Data were taken from recent peer-reviewed literature on Islamic political thought, maqasid, democracy, citizenship, governance, and public reason. Data collection was conducted through documentation, source selection, thematic classification, and critical reading. Data were analyzed through conceptual analysis and philosophical-hermeneutical interpretation to build a contextual model of Islamic political reasoning. The main finding shows that Islamic political thought needs to move from state-centric legalism toward an ethical-deliberative paradigm based on justice, welfare, plural citizenship, accountability, and non-coercive morality. The study concludes that Islamic political concepts remain relevant when reinterpreted through maqasid-oriented reasoning, democratic participation, and sensitivity to contemporary realities. This article contributes a conceptual model for developing Islamic political discourse that is ethical, inclusive, democratic, and responsive to modern public life.